Utility of Cardiac Magnetic Resonance with Pharmacological Stress to assess Myocardial Ischemia - Ramírez, Sara (2020)
Cardiovascular disease (CVD) represents the main cause of death in the world. According to the WorldHealth Organization (WHO), its prevalence is estimated to increase considering the high prevalence ofcardiovascular risk factors. In Peru, CVD remains the second cause of death in general population. Ischemiarepresents a strong predictor of future adverse events such as myocardial infarction and cardiovasculardeath. Accurate detection of ischemia exerts a pivotal role in the diagnostic strategy ofpatients with suspected coronary disease.Stress magnetic resonance is a non-invasive diagnostic tool, that offers advantage over other diagnostictechniques, considering that possesses high spatial resolution and no radiation exposure. Its diagnosticprecision for detecting coronary artery disease (CAD) is high, in addition of its prognostic valuein patients with suspicion of CAD.In this review we will describe how cardiac magnetic resonance with pharmacologic stress is performedin order to detect ischemia. We will also discuss the diagnostic and prognostic values of thistool in patients with suspicion of CAD.